Assessing the resilience of Mediterranean holm oaks to disturbances using selective thinning (Acta Oecologica, 2009)
Climate change will increase the frequency and the intensity of droughts in the Mediterranean region, likely reducing growth and increasing mortality of holm oaks (Quercus ilex), one of the most abundant species of Mediterranean forests. In water-limited systems such as those of the Mediterranean, carbon allocation patterns strongly favour belowground accumulation, especially in large subterranean structures called lignotubers. The resilience of these forests depends largely on the replenishment rate of these carbon reserves after disturbances. An experimental thinning, with two intensities (removal of 40% and 80% of basal area), was performed in 1992 in a holm oak forest at the Prades Experimental Complex of Catchments (NE Spain). In 2002, a second thinning was carried out in subplots within the former experimental 0.5 ha plots. Samples from the lignotubers of holm oak trees were analyzed for starch, and both mobile and immobile chemical components, in order to assess the resilience of holm oaks to repeated disturbances. Our results show that after 10 years, starch stocks in the lignotubers have only recovered to half their former values. Removing 40% of the basal area instead of 80% is suggested to be the better managing option for this kind of forests.